2014
DOI: 10.1002/2013jb010301
|View full text |Cite
|
Sign up to set email alerts
|

The Syabru‐Bensi hydrothermal system in central Nepal: 1. Characterization of carbon dioxide and radon fluxes

Abstract: The Syabru-Bensi hydrothermal system (SBHS), located at the Main Central Thrust zone in central Nepal, is characterized by hot (30-62°C) water springs and cold (<35°C) carbon dioxide (CO 2 ) degassing areas. From 2007 to 2011, five gas zones (GZ1-GZ5) were studied, with more than 1600 CO 2 and 850 radon flux measurements, with complementary self-potential data, thermal infrared imaging, and effective radium concentration of soils. Measurement uncertainties were evaluated in the field. CO 2 and radon fluxes var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 196 publications
(249 reference statements)
3
40
0
Order By: Relevance
“…Significant radon flux was observed in association with the CO 2 at all sites (Figure and Table ). Radon fluxes >1 Bq m −2 s −1 , similar to fluxes in the SBHS [ Girault et al ., ], were observed at Timure and Chilime, yielding radon discharges of 840 ± 170 and 290 ± 70 Bq s −1 , respectively, significant compared with the discharge in the SBHS (1600 ± 300 Bq s −1 ). In Dolpo, radon discharges were also significant (180 ± 40 and 70 ± 15 Bq s −1 ).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Significant radon flux was observed in association with the CO 2 at all sites (Figure and Table ). Radon fluxes >1 Bq m −2 s −1 , similar to fluxes in the SBHS [ Girault et al ., ], were observed at Timure and Chilime, yielding radon discharges of 840 ± 170 and 290 ± 70 Bq s −1 , respectively, significant compared with the discharge in the SBHS (1600 ± 300 Bq s −1 ). In Dolpo, radon discharges were also significant (180 ± 40 and 70 ± 15 Bq s −1 ).…”
Section: Resultsmentioning
confidence: 77%
“…In Figure , we compare these two parameters for our sites with more familiar instances of mofette sites and a selection of volcanic and hydrothermal sites (reviewed in Girault et al . []). The points of group I (SBHS, Timure, and Chilime) with significant discharge over a comparatively small surface area fall at the lower edge of the trend of volcanic and hydrothermal sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil moisture, porosity, temperature and atmospheric pressure affect transport within the soil pore space (Schery et al, 1984;Griffiths et al 2010;Sakoda et al, 2011;Barbosa et al, 2015) and Tanner (1964) showed that in a porous medium any combination of diffusion and convection will satisfy a simple diffusion model. Continuous, time resolved measurement of 222 Rn flux density and 222 Rn activity concentrations at several depths using active devices, coupled with simultaneous monitoring of other (meteorological) parameters, allow the influence of these parameters or the relative contributions of advection and diffusion to be evaluated (Ferry et al, 2001;Barbosa et al, 2015;Girault et al, 2014). In contrast passive, integrating devices are typically used in uranium exploration (Corner et al, 2009), for population dose assessment studies (Ramachandan and Sathish, 2011) or when longer term averages over large areas of heterogenous substrates are required the decay of 222 Rn in the open atmosphere, the progeny radionuclides may attach to aerosol particles or remain as unattached atoms.…”
Section: Introductionmentioning
confidence: 99%